Intraoperative PTH Assay during Minimally Invasive Parathyroidectomy May Be Helpful in the Detection of Double Adenomas and May Minimise the Risk of Recurrent Surgery - E. Ypsilantis; H. Charfare; W. S. Wassif (International Journal of Endocrinology)
Background. Minimally invasive parathyroidectomy (MIP) is increasingly replacing the traditional bilateral neck exploration in the treatment of primary hyperparathyroidism (PHP). Intraoperative PTH (IOPTH) measurement has recently been introduced as a useful adjunct in confirming successful excision of abnormal parathyroid gland. Aims. We evaluate the safety, efficacy, and clinical usefulness of IOPTH measurement during MIP in a district general hospital. Methods. Retrospective review of eleven consecutive patients with PHP who underwent MIP with IOPTH, following preoperative assessment with ultrasound and sestamibi scans. Results. All patients had successful removal of the abnormal parathyroid gland. The concordance rate between ultrasound and sestamibi scan in localising the parathyroid adenoma was 82%. IOPTH measurement confirmed the removal of adenoma in all cases and, in one case, led to identification of a second adenoma, not localised preoperatively. The median hospital stay was 2 days (range 1–7 days). All patients remained normocalcaemic after a median of 6 months (range 1–10 months). Conclusions. Minimally invasive parathyroidectomy is a feasible, safe, and effective method for treatment of PHP. The use of IOPTH monitoring potentially offers increased sensitivity in detecting multiglandular disease, can minimise the need and risk associated with recurrent operations, and may facilitate cost-effective minimally invasive surgery.